2019
DOI: 10.3390/medicina55060273
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin D Status in Diabetic Patients with Renal Disease

Abstract: Diabetes mellitus (DM) poses a major public health problem worldwide, with ever-increasing incidence and prevalence in recent years. The Institute for Alternative Futures (IAF) expects that the total number of people with type 1 and type 2 DM in the United States will increase by 54%, from 19,629,000 to 54,913,000 people, between 2015 and 2030. Diabetic Nephropathy (DN) affects about one-third of patients with DM and currently ranks as the first cause of end-stage kidney disease in the Western world. The compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 139 publications
1
33
0
Order By: Relevance
“…A variety of studies have shown that reducing urinary albumin excretion by inhibiting RAAS is associated with preservation of renal function. There is a better reduction in albuminuria when RAAS inhibitors are combined with VD in DN [40]. The VDR-KO mice were more susceptible to hyperglycemia-induced kidney damage [41,42].…”
Section: The Mechanism Of Vd/vdr In Diabetic Nephropathymentioning
confidence: 99%
“…A variety of studies have shown that reducing urinary albumin excretion by inhibiting RAAS is associated with preservation of renal function. There is a better reduction in albuminuria when RAAS inhibitors are combined with VD in DN [40]. The VDR-KO mice were more susceptible to hyperglycemia-induced kidney damage [41,42].…”
Section: The Mechanism Of Vd/vdr In Diabetic Nephropathymentioning
confidence: 99%
“…For example, vitamin D may help to maintain immune function, reduce the risk of respiratory infections and downregulate inflammatory cytokines, suggesting that deficiency could have a negative impact on Covid-19 outcomes [40,49]. Furthermore, vitamin D is a known regulator of cardiovascular and renal function mediated via the interaction of Vitamin D receptors within the renin-angiotensin-aldosterone system (RAAS), highlighting the multisystemic effects of vitamin D deficiency [50].…”
Section: Vitamin D Status By Season and Locationmentioning
confidence: 99%
“…Vitamin D exerts numerous pleiotropic effects unrelated to plasma calcium homeostasis. Indeed, various studies demonstrated that this hormone and its active analogs perform relevant anti-proteinuric, anti-fibrotic and anti-inflammatory actions in subjects with CKD and in experimental studies on animals with end-stage renal disease [11][12][13].…”
Section: Vitamin D: a Polymorphous Agent With Heterogeneous Functionsmentioning
confidence: 99%